1977
DOI: 10.1002/dev.420100612
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cortisol and temperature variation of normal and autistic children

Abstract: Blood samples and temperature measurements were taken over a 24-hr period for 6 children with autistic features and 3 normal control children of approximately the same age. The normal children showed relatively adult diurnal rhythmicity in cortisol and temperature. In contrast, 4 of 6 autistic children showed abnormal patterns in both measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 8 publications
4
20
0
Order By: Relevance
“…This finding of an HPA hyperresponsiveness is consistent with earlier reports of increased HPA responsivity to stress in autistic patients (Tordjman et al, 1998;Maher et al, 1975). On the other hand, the increase in cortisol levels during the control test may also be interpreted as a disturbance of the circadian rhythm of the HPA axis, as has been previously found in autistic subjects (Yamazaki et al, 1975;Hill et al, 1977;Hoshino et al, 1987). Although this may not explain the initial cortisol response after the public speaking test, since this response occurred at least 20 min earlier, it may have influenced the duration of the response after the public speaking test.…”
Section: Discussionsupporting
confidence: 92%
“…This finding of an HPA hyperresponsiveness is consistent with earlier reports of increased HPA responsivity to stress in autistic patients (Tordjman et al, 1998;Maher et al, 1975). On the other hand, the increase in cortisol levels during the control test may also be interpreted as a disturbance of the circadian rhythm of the HPA axis, as has been previously found in autistic subjects (Yamazaki et al, 1975;Hill et al, 1977;Hoshino et al, 1987). Although this may not explain the initial cortisol response after the public speaking test, since this response occurred at least 20 min earlier, it may have influenced the duration of the response after the public speaking test.…”
Section: Discussionsupporting
confidence: 92%
“…While recognizing that the studies examining cortisol in blood may be more confounded by the stress of such collection methods, they each have their own respective strengths (Curin et al, 2003;Hill et al, 1977;Nir, 1995). An earlier experiment, albeit small in sample size, was one of the only studies found that measured multiple overt rhythms in children with autism (Hill et al, 1977).…”
Section: Hormone Profiles In Children With Autismmentioning
confidence: 95%
“…Studies of cortisol rhythms in children with autism are somewhat inconclusive (Corbett et al, 2006(Corbett et al, , 2008Curin et al, 2003;Hill et al, 1977;Hoshino et al, 1987;Richdale and Prior, 1992;Tordjman et al, 1997), and findings may be influenced by the hormone's potentially confounding role in stress response (Corbett et al, 2006;Kirschbaum and Hellhammer, 1994). In order to minimize a potential masking by stress, most of the labs studying cortisol have chosen to employ saliva (Corbett et al, 2006(Corbett et al, , 2008Hoshino et al, 1987) or urine collection (Richdale and Prior, 1992) as opposed to blood (Curin et al, 2003;Hill et al, 1977). Outpatient studies in the child's home serve to further minimize stress by avoiding the need to be in a foreign environment, although control over study parameters may be compromised as well, such as the timing of sample collection.…”
Section: Hormone Profiles In Children With Autismmentioning
confidence: 98%
“…Cortisol is secreted by adrenal and as an indicator of stress (Morton, Anderson, Foggin, Kock, & Tiran, 1995;Schreck & Lorz, 1978). Many reports suggested that children with ASD showed alterations in the normal circadian patterns of cortisol (Hill, Wagner, Shedlarski, & Sears, 1977;Hoshino et al, 1987;Richdale & Prior, 1992;Tordjman et al, 1997). The associations between cortisol and RBs have been reported recently.…”
Section: Introductionmentioning
confidence: 97%